Introduction of Novel Drug Targets against Staphylococcus aureus and Proposing Putative Inhibitors against Adenine N1 (m1A22)-tRNA Methyltransferase (TrmK) using Computer-aided Drug Discovery - Beig, Masoumeh; Ebrahimi, Tahereh; Goodarzi, Narjes N.; Fereshteh, Sepideh; Habibi, Mehri; Badmasti, Farzad (Current Pharmaceutical Design, 2023)
Background: Nowadays, the emergence of methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant S. aureus (VRSA) strains has dramatically restricted the treatment options against this microorganism. Aim: In this study, we aimed to discover new drug targets and inhibitors against S. aureus. Methods: This study consists of two major sections. In the upstream evaluation, after a comprehensive coreproteome analysis, essential cytoplasmic proteins with no similarity to the human proteome were selected. Then the S. aureus metabolome-specific proteins were selected, and novel drug targets were identified using the DrugBank database. In the downstream analysis, a structure-based virtual screening approach was performed to reveal potential hit compounds against adenine N1 (m1A22)-tRNA methyltransferase (TrmK) using the StreptomeDB library and AutoDock Vina software. The compounds with a binding affinity > -9 kcal/mol were analyzed based on ADMET properties. Finally, the hit compounds were selected based on Lipinski’s rule of five (RO5). Results: Three proteins, including glycine glycosyltransferase (FemA), TrmK, and heptaprenyl pyrophosphate synthase subunit A (HepS1), were selected as feasible and promising drug targets based on PDB file availability and their essential role in the survival of the S. aureus. Finally, seven hit compounds, including Nocardioazine_ A, Geninthiocin_D, Citreamicin_delta, Quinaldopeptin, Rachelmycin, Di-AFN_A1 and Naphthomycin_ K were introduced against the binding cavity of TrmK, as a feasible drug target. Conclusion: The results of this study provided three feasible drug targets against S. aureus. In the following, seven hit compounds were introduced as potential inhibitors of TrmK, and Geninthiocin_D was identified as the most desirable agent. However, in vivo and in vitro investigations are needed to confirm the inhibitory effect of these agents on S. aureus.
Keywords: ADMET